An Evaluation of the Point-of-Care Test i-CHROMA Prostate-Specific Antigen Method for Screening in the Community. Issue 2 (June 2017) - Bolodeoku, John; Bains, Suman; Chand, Vivek; Bacon, Roger John; Weir, Peter; Miles, Vivian; Chinegwundoh, Frank
Abstract : Background: This study evaluated and compared the performance of the i-CHROMA point-of-care testing (POCT) method for the quantification of prostate-specific antigen (PSA) against a traditional laboratory PSA method (Abbott Architect assay). Materials and Method: Blood samples (venous [143] serum [143]) and finger prick (55) were collected from volunteers at a PSA screening campaign. Both venous and finger-prick samples were analyzed using the i-CHROMA PSA method and serum samples using the Abbott Architect method. Results were compared using linear regression and Red Amber Green analysis, a scoring system based on volunteer's age and PSA level. Red indicated a raised PSA, amber indicated a slightly raised PSA, and green indicated a normal PSA. Results: The data showed that both the i-CHROMA PSA results using the venous samples ( r 2 = 0.9841) and the finger-prick samples ( r 2 = 0.90845) showed a good correlation when compared with the serum samples using the laboratory method. The Red Amber Green analysis showed the i-CHROMA' venous PSA method identified 15 reds, 13 ambers, and 115 greens compared with 9 reds, 8 ambers, and 126 greens identified by Abbot Architect method. The i-CHROMA finger-prick PSA method identified 3 reds, 3 ambers, and 49 greens compared with 3 reds, 1 ambers, and 51 greens identified by Abbot Architect method. Conclusions: The i-CHROMA POCT PSA method showed good correlation with the Abbott Architect PSA method. Higher numbers of raised and abnormal PSA were identified by the i-CHROMA POCT PSA method due to the positive bias observed. The i-CHROMA POCT PSA method is a reliable method for total PSA within its limitations.